Green Highways: Harnessing Renewable Energy for Sustainable Power Generation with IoT Monitoring - Kumar Yegireddy, Narendra; N V S S Kumar, M; Santosh Kumar, Gottapu (International Journal of Psychosocial Rehabilitation, 2020)
In today's modern world, electricity plays a paramount role in our day-to-day existence. However, the stark reality is that our non-renewable energy sources are depleting at an alarming rate. Consequently, there is an urgent need to shift our focus from conventional energy sources to non-conventional, sustainable alternatives for electricity generation. The Dual Power Generation system represents an innovative solution that integrates both solar and wind energy plants, offering a reliable and uninterrupted power supply.This system capitalizes on the power of the wind, harnessing the pressure created by moving vehicles to rotate windmill blades and generate electricity. The wind turbulence experienced on highways is directly influenced by factors such as the size and speed of automobiles and the frequency of traffic. Simultaneously, the system taps into another abundant and free energy source, solar power generation. Solar panels are strategically positioned on dividers, enabling them to capture energy from sunlight during the day and even from vehicle headlights during the night.To ensure efficient operation and monitoring of both energy sources, a sensor network is employed, and the generated data is seamlessly uploaded to the cloud through the Internet of Things (IoT) technology. This dual approach not only addresses the growing energy demand but also promotes sustainability by reducing our reliance on depleting nonrenewable resources. It represents a visionary step towards a greener and more sustainable energy future.